A Rare Case of Female Urethral Diverticulum - Muhammad Iqbal; Yulia Margaretta Sari; Bobby Indra Utama (Fakultas Kedokteran Universitas Andalas, 2025)
Background: DU is a varied and challenging case of pelvic surgery because the diagnosis is difficult to make. Symptoms that appear in women vary, ranging from incidental findings, lumps or swelling, and pain in the vagina, as well as discharge from the urethra with a periurethral mass. Objective: In this report, we report a case of DU in a 32-year-old woman who complained of a painful lump in her genitals. This patient underwent transvaginal urethral diverticulectomy and successfully resolved the symptoms of urethral diverticulum he experienced. Methods: Management of urethral diverticulum in this report, namely by history taking, physical examination, supporting examination consisting of transvaginal and transperineal ultrasound, as well as cystourethroscopy before excision and reconstruction of the urethral diverticulectomy is carried out on this patient. Results: This patient had a successful transvaginal urethral diverticulectomy, with no early post-surgical complications found. Conclusion: Reducing the rate of problems following surgery is possible by adhering to the excision and reconstruction principles of urethral diverticulectomy.